A pan-cancer analysis of the prognostic value of long non-coding RNA LINC00662 in human cancers - Zhang, Guangming; Wu, Bin; Fu, Liangyin; Liu, Bin; Han, Xiaoyong; Wang, Jie; Zhang, Yipeng; Yu, Miao; Ma, Haizhong; Ma, Shixun; Cai, Hui (Frontiers in Genetics, 2022)
Background: Numerous studies have revealed that the long noncoding RNA LINC00662 is irregularly expressed in various cancers, as well as is correlated with cancer development and progression. Nevertheless, the clinical value of LINC00662 remains controversial. Hence, we explored the correlation of LINC00662 with cancer prognosis through meta-analysis and bioinformatics analysis. Methods: From the beginning through March 12, 2022, we searched for correlational studies on Web of Science, Embase, PubMed and The Cochrane library. We used pooled hazard ratios (HRs) and odds ratios (ORs) with 95% confidence intervals (CIs) to determine the significance of studies on survival outcomes and clinicopathological aspects in human cancers. Additionally, the Gene Expression Profiling Interactive Analysis (GEPIA) database was employed to confirm our findings. Results: Our meta-analysis of 14 studies comprising a total of 960 cancer patients revealed that LINC00662 overexpression was correlated with poor overall survival (HR = 1.91, 95% CI 1.49–2.45, P < 0.001) in cancer patients and recurrence-free survival (HR = 2.12, 95% CI 1.19-3.76, P = 0.010) in hepatocellular carcinoma patients. The correlation between LINC00662 and OS was further supported by the results of subgroup analyses according to cancer type, follow-up time, HR availability, and NOS score. In addition, LINC00662 overexpression predicted advanced tumor stage (OR = 4.23, 95% CI 2.50–7.17, P < 0.001), larger tumor size (OR = 1.49, 95% CI 1.11–1.99, P = 0.008), earlier lymph node metastasis (OR = 2.40, 95% CI 1.25–4.59, P = 0.008), and earlier distant metastasis (OR = 4.78, 95% CI 2.57–8.88, P < 0.001). However, there were no statistically significant differences in age (OR = 1.17, 95% CI 0.90–1.51, P = 0.246), gender (OR = 1.10, 95% CI 0.79–1.53, P = 0.578), or differentiation grade (OR = 1.53, 95% CI 0.71–3.33, P = 0.280). Conclusions: LINC00662 expression upregulation is associated with poor prognosis and advanced clinicopathological features in patients with multiple tumors. LINC00662 may serve as a biomarker for the diagnosis and treatment of patients with tumors.